Study on the effect of 40 Hz non-invasive light therapy system. A protocol for a randomized, double-blinded, placebo-controlled clinical trial - Agger, Mikkel Pejstrup; Horning, Maibritt; Carstensen, Marcus Schultz; Danielsen, Else Rubæk; Baandrup, Anders Olhues; Nguyen, Mai; Høgh, Peter; Miskowiak, Kamilla; Petersen, Paul Michael; Madsen, Kristoffer Hougaard; Kjær, Troels Wesenberg (Frontiers in Aging Neuroscience, 2023)
Introduction: With no cure or effective treatment, the prevalence of patients with Alzheimer's disease (AD) is expected to intensify, thereby increasing the social and financial burden on society. Light-based 40 Hz brain stimulation is considered a novel treatment strategy for patients with AD that may alleviate some of this burden. The clinical trial ALZLIGHT will utilize a novel Light Therapy System (LTS). The LTS uses Invisible Spectral Flicker for non-invasive induction of 40 Hz neural activity. This protocol describes a trial evaluating the efficacy and safety of a light-based 40 Hz brain stimulation in patients with mild-to-moderate AD. Methods: 62 patients with mild-to-moderate AD will participate in a randomized, double-blinded, placebo-controlled, parallel-group, and single-center trial. The participants will partake in an enrollment period of 1 month, an intervention period of 6 months, and a 1.5-month postinterventional follow-up period. Prior to the baseline measurement (week 0), the patients will be randomized to either active or placebo intervention. The primary endpoints will be the change of total This is a provisional file, not the final typeset article gamma power at 40 Hz from baseline (week 0), post-intervention follow-up (week 26), and nointervention follow-up (week 32) with and without concomitant stimulation with the device. Discussion: This protocol describes a randomized, double-blinded, placebo-controlled clinical trial that may increase the understanding of the effect of gamma oscillations in the human brain and how it could be utilized as a novel and important tool for the treatment of AD. The effect is measured through a large, multidisciplinary assessment battery. Clinical Trial Registration: www.ClinicalTrials.gov (NCT05260177). Registered on March 2, 2022.